2020
DOI: 10.28998/rca.v18i1.8006
|View full text |Cite
|
Sign up to set email alerts
|

EFEITO DA DESFOLHA NA ALTURA DE PLANTAS E PRODUTIVIDADE DE GRÃOS DE CANOLA (Brassica napus L.)

Abstract: A redução da área foliar das plantas interfere no potencial fotossintético e ocasiona perdas significativas no potencial de rendimento de grãos das culturas agrícolas. O objetivo desse trabalho foi avaliar o efeito da desfolha total na altura de plantas e produtividade final de grãos de canola em solo que apresenta má drenagem natural. Foi utilizado o delineamento inteiramente casualizado, com parcelas de 0,4 m de largura x 1 m de comprimento sub-subdivididas (trifatorial 2 x 4 x 4, onde fator A = solo com e s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 7 publications
0
4
0
2
Order By: Relevance
“…Zou et al (2014) and Nabloussi et al (2019) and 56.0% in Asia. In southern Brazil, Santos et al (2020) observed grain yield reductions of 194.9 kg ha -1 in soils without the removal of excess surface and subsurface water, whereas the use of drains increased the canola grain yield by 126.9%. Therefore, the drainage of excess surface water is essential to mitigate the adverse effects of rainy periods on canola-growing areas in poorly drained soils (Goulart et al, 2020).…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Zou et al (2014) and Nabloussi et al (2019) and 56.0% in Asia. In southern Brazil, Santos et al (2020) observed grain yield reductions of 194.9 kg ha -1 in soils without the removal of excess surface and subsurface water, whereas the use of drains increased the canola grain yield by 126.9%. Therefore, the drainage of excess surface water is essential to mitigate the adverse effects of rainy periods on canola-growing areas in poorly drained soils (Goulart et al, 2020).…”
Section: Resultsmentioning
confidence: 98%
“…Studies developed in the field by Zhou et al (2014) and Santos et al (2020) under waterlogging conditions, highlighted reductions in plant height of 50 and 57%, respectively. In a controlled environment, Rossi et al (2015) found similar results as the growth of canola plants was affected in aerated soil layers no deeper than 0.20 m, whereas restrictions at 0.10 m significantly compromised plant height.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Apresenta boa adaptabilidade aos sistemas de produção, como na rotação de culturas, reduzindo problemas fitossanitários (SANTOS et al, 2020), o que a torna uma excelente planta de cobertura no período do inverno. Além disso, a canola surge como uma alternativa econômica com a realização de sua semeadura como segunda safra anual, no período de outono-inverno, melhorando condições físicas do solo devido ao seu sistema radicular agressivo (HECK, 2015).…”
Section: Canolaunclassified
“…No Brasil, o cultivo da canola é realizado em mais de 35 mil hectares com produção superior a 43 mil toneladas (CONAB, 2020). O Rio Grande do Sul é o principal Estado produtor devido as condições ambientais de temperatura, radiação solar e precipitação favoráveis ao crescimento e desenvolvimento da cultura (DOS SANTOS et al, 2020).…”
Section: Introductionunclassified